THE ESSENCE OF CONSCIOUSNESS AND ITS GENESIS - Karimov , Bozarkul Khudaiberdiyevich (Innovative Development in Educational Activities, 2023)
The article describes the origin of mind, its multiversity and complexity, explains multilateral i.e. ontological, gynecological, social, pedagogical and psychological approaches that are necessary’ to understand the essence of mind. Also the article enlightens the harmony of mind with spirit, first of all with the forms of sense, intellect, imagination, thinking as well as physiological and psychoanalysis principles.